AT-TIJARAH (PERDAGANGAN) DALAM ALQURAN (Studi Komparatif Tafsir Jamiâ Li Ahkam Alquran dan Tafsir Al-Mishbah) - Fauziah, Cut (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Dawah of IAIN Langsa, 2017)
Trade always plays a vital role in the social and economic life of human beings of all tim, so that business interests will influence the behavior of all the individual, social, and any regional, national, and international. This studys is based on constituent concerns in view of the condition of trade problems both in the Islamic world in particular and the international community at large. The method used is the muqaran method to see the comparison between the opinion of al- Qurtubi and Quraish Shihab about tijarah  (trade) in the Quran so as to see visible differences or similarities, especially in terms of both methodology and interpretation. Therefore, the author of this study is expected to be able to analyze the opinion of al-Qurtubi and that of M. Quraish Shihab about tijarah (trade) and how hung of related to the principle of tijarah (trade) so as to formulate how to trade in accordance with the commandments of God and His Messenger. The equation of the two interpreters that they  equally say that the verses were revealed on issues discussed on tijarah (trade). In terms of methodology  they interpret the verse interpretation paragraph in accordance with the Quran, but the explanations are the different al-Qurtubi also use the narrations of the earlier scholars, historians and israiliyat narrators, and so forth, while Quraish Shihab explain these verses by including the views of previous scholars both from the clergy,  Sunni and Shiite ulama. Differences in interpretation between al-Qurtubi and Quraish Shihab verses above, al-Qurtubi said these verses describe tijarah (trade) over the fore with the legal aspects, it is seen as the interpretation that he did indeed use a style of interpretation fiqh , al-Qurtubi says that the origin of the fallacy is also known as the forgotten, forgot to get directions and to forget that which it is traded hints and error, so it is clear that al-Qurtubi put forward it directly to the trade laws of God that is with include guidance and misguidance. While the Quraish Shihab said that the trade should be established with a willingness between sellers and buyers, although compliance is nothing hidden in my heart, but the indicators and signs can be seen. Consent and granted or what is known in the customs of the handover are the forms that are used to demonstrate compliance.